Karl Ludwig von Knebel’s poems in the Journal von Tiefurth - Mönnich, Annette; Canal Pardo, Héctor (Revista de Filología Alemana, 2022)
Through his readings, numerous poems and translations, Karl Ludwig von Knebel provided valuable stimuli to the literary life in classical Weimar. During his absence (1781-1784) he maintained an intensive correspondence with his circle of friends in Weimar – which included not only Herder and Goethe, but also several poetically talented women. His poetry, with references to ancient, humanistic, and contemporary literature, contributed from afar to the Journal von Tiefurth. This handwritten periodical founded by the Duchess Mother Anna Amalia published the very different texts without indicating the author. The present article examines unsolved questions of authorship as well as typical intertextual references that were part of the game within the circle of authors and recipients.